From here, from there, and from beyond: endogenous and exogenous factors triggering change along the cluster life cycle in a multi-scalar environment - Dominik Santner; Dirk Fornahl (Philipps-University Marburg, Department of Geography, 2014)
While explaining cluster internal impacts on cluster development, cluster life cycle theory fails to explain the influence of cluster external factors. Based on a multiscalar approach, this study investigates factors causing change within an agritech cluster applying a qualitative approach. Main shifts in cluster development and their inducing factors from multiple scalar and thematic contexts are investigated. Concluding, incremental changes are mainly induced by knowledge dynamics within the same industry, especially from the local level. Radical change is the result of an exogenous shock from the national institutional environment. In total, specific changes are induced by specific factors from specific scales.
Keywords: L64; O31; O33; R11; 330; endogenous factors; exogenous factors; cluster development; multiscalarity; cluster life cycle